(a) use substitution
change 5x-y=11 to y =5x-11
then substitue that into the other equation
3x+ 2(5x-11)=4
3x+ 10x-22=4
13x-22=4
13x=26
x=2
plug back in
5x-y=11
5(2)-y=11
10-y=11
-y=1
y=-1
(b) do the same thing and subsitute, this time you do not have to change an equation
3x+ (-3x-5) =2
3x -3x -5=2
-5=2
this equation does not work and has no solution (since both sides are not equal)
hope I helped!
email me if you have any more questions...it should be on my profile
~SmS~
ADDED
Elimination process-
5x-y=11
3x+2y=4
multiply both equations to make one of the variables additive inverses
2(5x-y)=2(11)
1(3x+2y)=1(4)
10x-2y=22
3x+2y=4
then eliminate the y
13x=26
then solve,
x=2
plug back in...
5x-y=11
5(2)-y=11
10-y=11
-y=1
y=-1
The solution to (a) is (2,-1)
Using this, you can probably do (b). You just have to change the 2nd equation to a+b=c format
it would be 3x+y=-5
2006-10-14 21:26:40
·
answer #1
·
answered by ♥Pyar Ki Pari♥ 4
·
0⤊
0⤋
Since the equations are in two variables, two seperate non-reducing propositions are necessary for the equations to be solved simultaneously as given here. Then,
a) 5x - y =11 --------(1)
3x + 2y = 4 -------(2)
Now multiply equation (1) by a scalar 2, note that 2 is the coefficient of the variable y in equation (2)
(1) *2 gives, 10x - 2y = 22 ------(3)
Let this new relation(which is reducible to (1)) be (3)
then,
(2) + (3) gives,
13x = 26 => x = 2
Notice how we take out one variable so that we may work with the other.
Since we know now that x=2, plug this value to any of the equations (1), (2) or (3) and they will each give you a single value for y. Consider (1) then,
x =2 => 5(2) - y =11
then, y = 10 -11 = -1
so x =2 , y=-1
Try b) 3x + y = 2 -----(1)
y = -3x -5 ------(2)
Now consider (2), if you *** 3x to both sides you get,
3x+y = -5
but the first equation says 3x+y = 2
both relations cannot hold at the same time so the claims are false having been presented simultaneously.
If however this was a typography error, the first example will allow you to solve a new two variable system of linear equations.
2006-10-15 04:51:40
·
answer #2
·
answered by yasiru89 6
·
0⤊
0⤋
Question B cannot be performed as you have written down.
I don't konw how advanced you are so I will be very thorough.
Question A can be as follows:
5x-y=11 - equation 1
3x+2y=4 - equation 2
Multiply one of these equations by an amount so that it makes a pronumeral (a letter, x or y) the same quantity as the other equation.
I chose to multiply equation 1 by 2
this turns equation 1 into
10x-2y=22 - new equation 1
3x+2y=4 - equation 2
Add the 2 equations together. This forms equation 3. Notice the y's cancel out.
13x=26
which means
x=2
sub back into equation 2 to check what y equals.
3x+2y=4
3(2)+2y=4
6+2y=4
2y=4-6
2y=-2
y=-1
So x=2, y=-1 which can be written as (2, -1) Good luck with the rest.
2006-10-15 07:05:48
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
(a)
5x - y = 11
3x + 2y = 4
Multiply the 1st equation by 2
10x - 2y = 22
3x + 2y = 4
Add:
13x = 26
Solve for x, substitue into either equation, and solve for y.
(b)
This pair is nonsensical. They cannot be solved as written. You end up with -5 = 2, which is untrue.
2006-10-15 04:24:29
·
answer #4
·
answered by Helmut 7
·
0⤊
0⤋
Don't you just want to use substitution or subtraction??
a) y = -11 +5x (sub into 3x + 2y = 4)
3x + 2(-11 +5x) = 4
x = 2 y = -1
b) y= -3x - 5 (sub into 3x + y =2)
3x + (-3x -5) = 2
(Cant solve this last one, did you write it down wrong??)
2006-10-15 04:08:32
·
answer #5
·
answered by Tyler D 2
·
0⤊
0⤋
for 1st eq
5x-y=11 *2
3x+2y=4
10x-2y=22
3x+2y=4
13x=26
x = 2
5(2)-y=11
y= -1
2nd eq maybe is typed wrong checkout
2006-10-15 04:30:19
·
answer #6
·
answered by sahi 2
·
0⤊
0⤋